Entrepreneurship Potential Among Undergraduates in Nigerian Universities : Empirical Evidence - Adelowo, Caleb M.; Joshua, Abimbola A.; Ilevbare, Oluwatosin E. (AMC Indian Journal of Entrepreneurship, 2018)
Development experts have argued that entrepreneurship education (EE) equips students for job creation and reduces the rate of graduate unemployment. Several studies examined entrepreneurial interest and practice among the undergraduates in Nigeria before and after the introduction of compulsory entrepreneurship education in 2006. However, the perception of students on EE and university entrepreneurship ecosystem has not been investigated. This article presents the results of a recent study conducted on undergraduates of two purposively selected universities in Nigeria with a view to suggesting appropriate practical measures to improve entrepreneurship climate in these schools and harness entrepreneurship potential of students even before graduation. The results show very high entrepreneurial interest among students while few of them are practising entrepreneurship. Majority of these students have taken entrepreneurship course, supporting government directives. Those who had taken entrepreneurship course were able to confirm that the course was useful; it particularly increased their business skills and knowledge, helped them develop networks and equipped them with the ability to identify business ideas. The entrepreneurship ecosystem in the school provides a very good atmosphere for knowledge acquisition but there are little facilities for practical entrepreneurship actions. The article concludes that the National Universities Commission's directives should be monitored for effectiveness. Practical entrepreneurship facilities can be established to harvest Â entrepreneurship ideas among students. University entrepreneurship ecosystem requires sufficient boost to ensure the transition of intentions of students into entrepreneurial actions.